1992
DOI: 10.2166/wst.1992.0382
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Consequences of the Gulf War in Kuwait: Impact on Water Resources

Abstract: As a result of the Iraqi occupation and the armed conflict in Kuwait 6 to 8 million barrels of crude oil were spilled into the marine environment, and about 2 to 3 million barrels of crude oil, burnt and unburnt, were being emitted daily during about 300 days into the environment from the burning or gushing oil wells. International efforts of UN agencies and other organizations from, the region and outside started immediately to assess the extent of the environmental pollution and to mitigate the adverse effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…4-7). Selective ground truth has been carried out by Kuwait Institute for Scientific Research (Literathy, 1992(Literathy, , 1993Al Sarawi et al, 1998;Kwarteng, 1998Kwarteng, , 1999AlDousari, 2001). The intra-image LST variations were verified from the collated ground truth data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4-7). Selective ground truth has been carried out by Kuwait Institute for Scientific Research (Literathy, 1992(Literathy, , 1993Al Sarawi et al, 1998;Kwarteng, 1998Kwarteng, , 1999AlDousari, 2001). The intra-image LST variations were verified from the collated ground truth data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The spilled crude oil was converted to a hard residue containing high concentrations of toxic PAHs (Literathy, 1992) due to the intensive evaporation and photooxidation processes typical of Kuwait's environment 2. A thin layer of fine dust that originated from nearby areas has been formed on the surface of oil lakes due to the high annual dust fallout in Kuwait [lmm/year, (Khalaf and Al-Hashash, 1983)].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, dry oil residues can be resuspended with dust by the action of wind erosion and reach human receptors. Literathy (1992) reported that, in some areas of Kuwait's desert, natural weathering has converted the spilled crude oil to a hard residue containing high concentrations of toxic PAHs. Although large amounts of oil from the lakes have been removed, the remaining portion has thickened as a result of long periods of weathering.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of burning and gushing oil from the damaged wells was estimated between 2 to 4 million barrels per day for a period of over 300 days. The total amount of oil spilled into the Gulf is estimated between 6 to 8 million barrels (2).…”
Section: Introductionmentioning
confidence: 99%